2021
DOI: 10.3390/molecules26237255
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation-Enhanced Room-Temperature Phosphorescence from Au(I) Complexes Bearing Mesogenic Biphenylethynyl Ligands

Abstract: Gold(I) complexes, enabling to form linear coordination geometry, are promising materials for manifesting both aggregation-induced emission (AIE) behavior due to strong intermolecular Au–Au (aurophilic) interactions and liquid crystalline (LC) nature depending on molecular geometry. In this study, we synthesized several gold(I) complexes with rod-like molecular skeletons where we employed a mesogenic biphenylethynyl ligand and an isocyanide ligand with flexible alkoxyl or alkyl chains. The AIE behavior and LC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…To further investigate this behavior, POM images were collected to examine the optical texture of Cbz-H (Figure 3). A schlieren texture was obtained at 93 • C, which confirmed that the observed phase for Cbz-H is the N phase [14,16]. In the DSC thermogram, a small endothermic peak was observed at 73 • C during the heating process, and an isotropic phase was achieved at 118 • C. The N phase was observed between these temperatures.…”
Section: Thermal Behavior Of Complex Cbz-rsupporting
confidence: 70%
See 3 more Smart Citations
“…To further investigate this behavior, POM images were collected to examine the optical texture of Cbz-H (Figure 3). A schlieren texture was obtained at 93 • C, which confirmed that the observed phase for Cbz-H is the N phase [14,16]. In the DSC thermogram, a small endothermic peak was observed at 73 • C during the heating process, and an isotropic phase was achieved at 118 • C. The N phase was observed between these temperatures.…”
Section: Thermal Behavior Of Complex Cbz-rsupporting
confidence: 70%
“…The C1-Au-C2 bond angle is ~180 • [21], and molecular packing gives a Au-Au bond distance of 6.4 Å, which suggests the absence of aurophilic interactions between the molecules. We have previously reported the structure of a similar Au(I) complex that has less-hindered 4-ethynylbiphenyl and alkyl isocyanide ligands [14]. This complex also crystallized in triclinic space group Pī, and the C1-Au-C2 bond angles were the same as in Cbz-H, i.e., ~180 • ; however, the intermolecular Au-Au distance was 3.46 Å, which confirms the presence of intermolecular aurophilic interactions in the crystal.…”
Section: Synthesis and Characterization Of Complex Cbz-rmentioning
confidence: 99%
See 2 more Smart Citations
“…Luminescent liquid crystals (LLCs) combine the luminescence properties and ordered structures of liquid crystals. LLCs are mainly divided into two categories: fluorescent liquid crystals and phosphorescent liquid crystals. In recent years, room-temperature phosphorescent (RTP) liquid crystals have attracted increasing attention because of their important application prospects in phosphorescent organic light-emitting diodes (OLEDs), polarized light emitting materials, anticounterfeiting materials, and other fields. Early research on RTP liquid crystal materials mainly focused on heavy metal complexes. This is because the metal–ligand charge transfer can cause effective spin–orbit coupling (SOC), thereby enhancing the intersystem crossing (ISC) process to populate triplets. It is inevitable that these heavy metal complex RTP materials are usually toxic, environmentally unfriendly, and expensive, and therefore, it is highly desirable to develop pure organic RTP liquid crystal materials.…”
Section: Introductionmentioning
confidence: 99%